2016
DOI: 10.2196/ijmr.5590
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Difficulties in Daily Activities and Falling: Loco-Check as a Self-Assessment of Fall Risk

Abstract: BackgroundPeople aged 65 years or older accounted for 25.1% of the Japanese population in 2013, and this characterizes the country as a “super-aging society.” With increased aging, fall-related injuries are becoming important in Japan, because such injuries underlie the necessity for nursing care services. If people could evaluate their risk of falling using a simple self-check test, they would be able to take preventive measures such as exercise, muscle training, walking with a cane, or renovation of their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In activities of daily living, previous studies have reported that locomotive syndrome and sarcopenia are associated with ADL performance 9,10) . For example, one study found that decreased rapid walking speed for females aged ≥65 years was associated with incident ADL disability 21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In activities of daily living, previous studies have reported that locomotive syndrome and sarcopenia are associated with ADL performance 9,10) . For example, one study found that decreased rapid walking speed for females aged ≥65 years was associated with incident ADL disability 21) .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that participants who have fallen or who have gait or balance problems are at higher risk of future falls 17) . Both locomotive syndrome and sarcopenia are associated with fall risk 9,10) . In the present study, TUG time in the L+S group was significantly longer than those in CON and L groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in a selection bias of subjects. However, web surveys have recently become a common method of conducting research [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that a larger number of items with an answer of “yes” on the loco-check was significantly associated with reduced health-related quality of life (HRQoL) assessed by the EuroQoL-5 dimensions (EQ-5D) and EuroQoL-visual analog scale (EQ-VAS) 6 ) . Furthermore, the number of times that “yes” was selected on the loco-check has been found to be significantly correlated with the experience of falling in the previous year 7 ) .…”
Section: Introductionmentioning
confidence: 99%